Nuclear Magnetic Resonance Spectroscopic Study of Organic Components Extracted from Manures and Soils under Different Land Uses in Gujarat - and S. Raghothama, S. Tripathi, Narendra Singh, Srinivasa, A. Bafna (Journal of the Indian Society of Soil Science, 2015)
Humic substances play important role in many biogeochemical cycles. Knowledge of their chemical composition and their interactions with other properties is useful for understanding soil fertility. In this study we have extracted humic acid (HA) from two organic manures namely, farmyard manure (FYM) and vermicompost and the soils from different production systems viz., cultivation with sapota, mango and banana and soils from organic farm of the Navsari Agricultural University. These were characterized by 1H NMR and 13C NMR spectroscopy. Due to poor solubility of some soil samples, 13C CPMAS spectra were recorded in solid state. The comparison of spectra of extracted HA revealed some common characteristic NMR signals, but magnitudes of these peaks were different. These characteristic peaks were also reported by various authors in the past and indicated presence of characteristic chemical groups in HA. All HA indicated input from lignin, cellulose, hemicelluloses and other plant degradation products in their chemical composition. Organic manure HA were found different from the soil HA spectra mainly in proportion of carbon content in different functional group. All HA indicated more aliphatic character in the spectra pointing towards their early stage of formation due to a larger H/C ratio and they are labile and may be rapidly degraded by microorganisms.